2012
DOI: 10.1111/j.1365-2796.2012.02530.x
|View full text |Cite
|
Sign up to set email alerts
|

Anti‐apolipoprotein A‐1 IgG in patients with myocardial infarction promotes inflammation through TLR2/CD14 complex

Abstract: Abstract. Pagano S, Satta N, Werling D, Offord V, de Moerloose P, Charbonney E, Hochstrasser D, Roux-Lombard P, Vuilleumier N

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
130
1
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 72 publications
(140 citation statements)
references
References 45 publications
8
130
1
1
Order By: Relevance
“…[149][150][151][152] In fact, there was an association between high anti-apoA-I IgG titers and increased circulating levels of oxidized LDL, TNF-α, IL-6, IL-8, and matrix metalloproteinase 9 (MMP-9). 150,153,154 Accordingly, patients positive for serum anti-apoA-I IgG had decreased plaque stability, as evidenced by increased intraplaque MMP-9 levels as well as higher densities of macrophages and neutrophils within plaques. 151 These clinical findings are corroborated by in vivo and in vitro data showing that apoE-deficient mice immunized with anti-apoA-I IgG developed larger, more vulnerable atherosclerotic lesions with higher neutrophil and MMP-9 contents and reduced collagen content, displayed signs of myocardial injury, and had higher mortality rates than apoEdeficient mice treated with a control IgG.…”
Section: Anti-apoa-i Autoantibodiesmentioning
confidence: 99%
See 2 more Smart Citations
“…[149][150][151][152] In fact, there was an association between high anti-apoA-I IgG titers and increased circulating levels of oxidized LDL, TNF-α, IL-6, IL-8, and matrix metalloproteinase 9 (MMP-9). 150,153,154 Accordingly, patients positive for serum anti-apoA-I IgG had decreased plaque stability, as evidenced by increased intraplaque MMP-9 levels as well as higher densities of macrophages and neutrophils within plaques. 151 These clinical findings are corroborated by in vivo and in vitro data showing that apoE-deficient mice immunized with anti-apoA-I IgG developed larger, more vulnerable atherosclerotic lesions with higher neutrophil and MMP-9 contents and reduced collagen content, displayed signs of myocardial injury, and had higher mortality rates than apoEdeficient mice treated with a control IgG.…”
Section: Anti-apoa-i Autoantibodiesmentioning
confidence: 99%
“…151,155 Furthermore, incubation of human monocytederived macrophages with anti-apoA-I IgG under cell culture conditions resulted in increased production of cytokines (TNF-α, IL-6, IL-8), matrix metalloproteinases (MMP-9), and monocyte chemoattractants (CCL2, CXCL8). 151,153,154 Blocking experiments revealed that anti-apoA-I IgG-induced inflammatory responses in macrophages are mediated mainly via the CD14/TLR2 complex and to a lesser extent via TLR4. 154 Consistent with a role for TLR2 and TLR4 in the pro-atherosclerotic effects of anti-apoA-I antibodies, the augmented atherosclerotic plaque vulnerability, myocardial necrosis, and mortality in response to antiapoA-I IgG passive immunization are abrogated in TLR2-and TLR-4-deficient mice.…”
Section: Anti-apoa-i Autoantibodiesmentioning
confidence: 99%
See 1 more Smart Citation
“…These antibodies are capable to bind to TLR2 and influence intracellular signaling in a TLR2/CD14-dependent manner. 100 The ability of ApoA1 self-antibodies to recognize TLR2 arises from the partial homology between TLR2 and ApoA1 a.a. sequences that therefore induces crossreactivity. 100 Indeed, the presence of a partial homology between TLR2 and ApoA1 a.a. sequences presumes the possibility that anti-apoA-1 IgG response can take place from a pathogen exposure cannot be excluded.…”
Section: Proatherogenic Functional Effects Of Antiapoa1 Self-antibodimentioning
confidence: 99%
“…100 The ability of ApoA1 self-antibodies to recognize TLR2 arises from the partial homology between TLR2 and ApoA1 a.a. sequences that therefore induces crossreactivity. 100 Indeed, the presence of a partial homology between TLR2 and ApoA1 a.a. sequences presumes the possibility that anti-apoA-1 IgG response can take place from a pathogen exposure cannot be excluded. In addition, antibody-dependent stimulation of TLR2 leads to secretion of inflammatory mediators such as IL (interleukin)-6, IL-8, tumor necrosis factor (TNF)-α, MMP-9, and chemokine (C-C motif) ligand 2 by macrophages derived from MI patients.…”
Section: Proatherogenic Functional Effects Of Antiapoa1 Self-antibodimentioning
confidence: 99%